Halal Tourism Development Strategies in Semarang City: The Role of the Department of Culture and Tourism - Ahmadi, Erwin; Choliq, Abdul; Suryorini, Ariana (Halal Science, 2026)
Halal tourism development in Indonesia has strong economic potential; however, its implementation remains uneven across regions due to fragmented governance and limited stakeholder integration. This study aims to analyze halal tourism development in Semarang City by examining institutional roles, supporting and inhibiting factors, and implementation mechanisms. A qualitative descriptive approach was applied using purposive sampling, with data collected through in-depth interviews, field observations, and document analysis. The findings, derived from interviews with government officials, tourism stakeholders, and field observations of tourism services, show that halal tourism development in Semarang is supported by inter-agency collaboration, cross-sectoral coordination, and digital promotion strategies. Field evidence indicates that coordination between tourism and food-related agencies plays a key role in accelerating SME halal certification support, while tourism sites have gradually integrated Muslim-friendly services such as prayer facilities and halal food information systems. However, challenges remain, particularly related to differing perceptions of halal tourism among industry actors, uneven institutional coordination, and limited human resource capacity. These findings highlight that implementation gaps are not only structural but also shaped by stakeholder understanding and operational readiness at the local level. In addition, SME halal certification support and the strengthening of halal value chains remain important determinants of tourism performance in the city. The study contributes to halal tourism governance literature by emphasizing the role of micro-level coordination and stakeholder perception in shaping policy implementation outcomes, while practically suggesting stronger inter-agency coordination, clearer communication of halal tourism concepts, and targeted capacity-building programs for tourism actors.